1999
DOI: 10.1063/1.123423
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing defect-related photoluminescence by hot implantation into SiO2 layers

Abstract: Visible photoluminescence around an orange band of 580 nm wavelength are observed from 300 nm thin SiO2 layers implanted by Si or Ge ions at both substrate temperatures of 25 °C [room temperature (RT)] and 400 °C (hot). Si implantations at an energy of 30 keV were performed with doses of 5×1015, 3×1016, and 1×1017 cm−2 while Ge implantations were done at 100 keV with a dose of 5×1015 cm−2. Samples implanted at 400 °C always show much higher intensities of luminescence than those implanted at room temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…21 The formation of Er/Er-oxide clusters with dimensions of 2-5 nm has also been examined in both S Er and S NC+Er systems. 28,30 It is worthwhile to note that the Si= O double bonds have been reported at the surface of amorphous silica 33 as well as at the interface between the surface oxide layer and the Si substrate. 3͑b͒.…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…21 The formation of Er/Er-oxide clusters with dimensions of 2-5 nm has also been examined in both S Er and S NC+Er systems. 28,30 It is worthwhile to note that the Si= O double bonds have been reported at the surface of amorphous silica 33 as well as at the interface between the surface oxide layer and the Si substrate. 3͑b͒.…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
“…3͑a͔͒. 10,11,[28][29][30][31] Defects such as radiative nonbridging oxygen-hole center ͑NBOHC͒ ͑O 3 ϵ Si-O·͒ has been proposed and shown to emit light ϳ580 nm. In addition, the contrast of Si NCs is relatively low in amorphous SiO 2 .…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors also observed a red or infrared PL between 1.3 and 1.9 eV after high-temperature annealing of Si-implanted oxides [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In [27] it was shown, that the observed emission photon energy of Si-implanted oxides could be tuned between 1.4 and 1.8 eV by varying the annealing time in oxygen at 1000 • C. Im et al implanted thermally grown SiO 2 layers with Si at RT and at 400 • C, and found that the implantation at 400 • C increases the intensity of the yellow PL by 50% to 100% [29]. Chou et al performed rapid thermal annealing (RTA) with T ≥ 950 • C on Si-implanted SiO 2 films in dry and wet N 2 atmosphere leading to the appearance of a PL peak at 2.2 eV and 1.9 eV, respectively [21].…”
Section: Luminescence Of Ion-implanted Sio 2 Layersmentioning
confidence: 99%
“…In addition to the limited space of such nanocrystals, which facilitates radiative recombination, an oxide layer also provides defect sites to aid this process. Accordingly, many processes such as co-sputtering [3], ion implantation [4,5], and annealing [6] have been reported to fabricate nanostructured Si or Ge embedded in an oxide matrix to make visible-light emissions possible.…”
Section: Introductionmentioning
confidence: 99%